BDNF Val66Met in preclinical Alzheimer's disease is associated with short-term changes in episodic memory and hippocampal volume but not serum mBDNF - Lim, Y.; Rainey-Smith, S.; Lim, Y.; Laws, Simon; Gupta, V.; Porter, T.; Bourgeat, P.; Ames, D.; Fowler, C.; Salvado, O.; Villemagne, V.; Rowe, C.; et al. (Cambridge University Press, 2017)
Copyright Â© International Psychogeriatric Association 2017. Background: The brain-derived neurotrophic factor (BDNF) Val66Met polymorphism Met allele exacerbates amyloid (AÎ²) related decline in episodic memory (EM) and hippocampal volume (HV) over 36-54 months in preclinical Alzheimer's disease (AD). However, the extent to which AÎ²+ and BDNF Val66Met is related to circulating markers of BDNF (e.g. serum) is unknown. We aimed to determine the effect of AÎ² and the BDNF Val66Met polymorphism on levels of serum mBDNF, EM, and HV at baseline and over 18-months. Methods: Non-demented older adults (n = 446) underwent AÎ² neuroimaging and BDNF Val66Met genotyping. EM and HV were assessed at baseline and 18 months later. Fasted blood samples were obtained from each participant at baseline and at 18-month follow-up. AÎ² PET neuroimaging was used to classify participants as AÎ²- or AÎ²+. Results: At baseline, AÎ²+ adults showed worse EM impairment and lower serum mBDNF levels relative to AÎ²- adults. BDNF Val66Met polymorphism did not affect serum mBDNF, EM, or HV at baseline. When considered over 18-months, compared to AÎ²- Val homozygotes, AÎ²+ Val homozygotes showed significant decline in EM and HV but not serum mBDNF. Similarly, compared to AÎ²+ Val homozygotes, AÎ²+ Met carriers showed significant decline in EM and HV over 18-months but showed no change in serum mBDNF. Conclusion: While allelic variation in BDNF Val66Met may influence AÎ²+ related neurodegeneration and memory loss over the short term, this is not related to serum mBDNF. Longer follow-up intervals may be required to further determine any relationships between serum mBDNF, EM, and HV in preclinical AD.